Establishing evidence-based practices in disability services - Tankersley, Melody (Social Welfare: Interdisciplinary Approach, 2013)
Article presents the theoretical understanding of usage of evidence-based practices in disability service promoting the most effective of practices. The details of identifying, promoting, and implementing EBPs involve a plethora of potentially problematic issues. Detail discussed purports of quality and quantity of the research describes wide application fi eld of EBP. Criterion-based frameworks for determining effective or evidence-based practices could be used as a practical guide in disability services. The essential steps in determining whether a practice is evidence-based seem to be (a) locating the high quality, experimental research that examines the effectiveness of the practice and then (b) determining whether suffi cient quantity of evidence showing that the practice causes improved outcomes exists are discussed as well.